CHANGING EVERYTHING: CLOUD PATIENTS HEALTH MONITORING & 24-HOUR CARE OVER BODY SENSOR NETWORK - MOHAMMED AYAZ.R; SADAF ZABEEN; R. RAJKUMAR (International Journal of Pharma and Bio Sciences, 2016)
Each and every vital sign has a direct impact on healthcare, so body sensors are used for constant healthcare monitoring. In existing methods, the sensors are implanted or wear by the user and the sensor data is transferred through PDA (personal digital assistant) and stored in the medical server. In this proposed system is for a hospital environment the doctors and nurses can get access to the user’s medical information from the server. The wearable sensor’s on the patient’s body is connected to an Arduino board the sensed information is transmitted by relay node and stored in the cloud. The doctors and nurses can access the patient’s medical information from cloud.